"Una giornata al mare" : een keuze uit de verzameling van Geertjan Visser. - Oxenaar, R.W.D (Otterlo : Rijksmuseum Kröller-Müller, 1992)
Andre, Carl ; Baselitz, Georg ; Broodthaers, Marcel ; Dibbets, Jan ; Dokoupil, Georg Jiri ; van Elk, Ger ; Fontana, Luciano ; Gilbert and George ; Holzer, Jenny ; Judd, Donald ; Kelly, Ellsworth ; Kiefer, Anselm ; Kosuth, Joseph ; Kunc, Milan ; Long, Richard ; Manzoni, Piero ; De Maria, Walter ; Martin, Agnes ; Nauman, Bruce ; Penck, A.R. ; Picabia, Francis ; Ryman, Robert ; Stella, Frank ; Visser, Carel ; Warhol, Andy ; Weiner, Lawrence
"Una giornata al mare" : een keuze uit de verzameling van Geertjan Visser, Rijksmuseum Kröller-Müller, Otterlo, 27.6. - 1.11.1992
boek